Parental support and involvement in school - Hertel, Silke; Jude, Nina (Assessing contexts of learning, 2016)
In recent years, the involvement of parents in educational processes has gained importance in the educational debate, and has also become increasingly relevant in educational policy. Parents are powerful stakeholders in education; thus, information on parents’ opinions and engagement is highly valuable in large-scale assessments like the Programme for International Student Assessment (PISA). PISA can deliver information about educational processes at home, as well as parents’ needs, demands, and expectations of their interaction with schools, by addressing the parents directly. This also allows for analysing relationships between variables from the parent questionnaire and students’ achievements and motivations, affording insights into differences between groups (such as high- and low-performing students), and questions of equity. Furthermore, on the basis of PISA data, information about policies at the system level can be gained: that is, how parental engagement is supported through school policies or national intervention programs. Additionally, more detailed information about home learning environments can be gained from parents’ answers. In PISA 2015, a theory-based approach was chosen to systemize and to enhance aspects of parental involvement in children’s education. Following a theoretical model of the parental involvement process (Green et al. 2007), questions on parents’ home- (e.g. helping with homework) and school-based (e.g. helping in the school library, talking to the teacher) involvement strategies, as well as factors influencing parental involvement (e.g. parents’ beliefs and motivations, perceptions of invitations from school) were included. To gain a multi-perspective view on parental involvement, targeted items were added to the parent, school, student and teacher questionnaires.
Gesehen am 25.02.2026